Survey for the presence of pathogenic fee-living amoeba in man - Cauyan, Gil A.
A survey was undertaken to determine whether free-living amoeba is present in man in the Philippines. A total of 2,101 subjects consisting of meningitic and meningoencephalitic patients, slum-dwellers, public elementary school children and persons living near a canal in Chicago St., Quezon City found positive for free-living amoebae pathogenicc to mice were imcluded in the survey. Nasal and throat swabs collected from the subjects were cultured in distilled water with Escherichia coli and examined after 7 days by direct microscopy for the presence of free-living amoeba.